1999
DOI: 10.1046/j.1525-1489.1999.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Noise in the Pediatric Intensive Care Unit

Abstract: The pediatric intensive care unit is an environment filled with dedicated caregivers, state‐of‐the‐art monitors, and machines that collectively work to provide the best care possible for critically ill children. A previously unappreciated result of having these resources mingled together is the elevated level of environmental noise. Although the levels of noise do not reach OSHA levels (>85 dB for 8 continuous hours) that cause noise‐induced hearing loss, the patients are exposed to continuous moderate noise l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Studies in paediatric intensive care units have shown that noise routinely disrupts sleep that is necessary for patient comfort or recovery. 18 The nature of sound and its reverberation rate (how long the sound remains) has a direct effect on the noise level. When the reverberation rate is long there is greater opportunity for sounds to blend together, increasing the noise level.…”
Section: Noise Reductionmentioning
confidence: 99%
“…Studies in paediatric intensive care units have shown that noise routinely disrupts sleep that is necessary for patient comfort or recovery. 18 The nature of sound and its reverberation rate (how long the sound remains) has a direct effect on the noise level. When the reverberation rate is long there is greater opportunity for sounds to blend together, increasing the noise level.…”
Section: Noise Reductionmentioning
confidence: 99%